Spatial Distribution of Malaria Vector Breeding Sites in Purworejo District Central Java Province: Distribusi Spasial Habitat Perkembangbiakan Vektor Malaria di Kabupaten Purworejo Provinsi Jawa Tengah - Sunaryo; Ikawati, Bina; Wijayanti, Tri (Aspirator, 2021)
Malaria is the main health problem in Purworejo District, especially in the hilly areas which are bordered by Magelang District (Central Java Province) and Kulonprogo District (Yogyakarta Special Region), Those are identified as malaria receptive areas. Malaria vector breeding sites were found in nearby settlements and occur every season, resulting in the transmission of malaria throughout the year. Spatial mapping of malaria vector breeding sites could support tracing and follow-up of malaria vector control interventions in malariaendemic areas. Survey and mapping of malaria vector breeding site were done using Global Positioning System (GPS) and the data obtained were processed with ArcGIS. The research was conducted in April – November 2018 in Purworejo. This research shows that vector breeding sites in the dry season are puddles along rivers and springs around settlements; small breeding sites with few water volumes. The breeding sites are in the shade of plants or trees. The appropriate intervention measures are action to dry the malaria vector breeding sites, protection of springs and puddles through larvacidation in the dry season, and mosquito nets using in communities around the malaria vector breeding sites. This research concludes the malaria vector breeding sites at dry season concentrates along the rivers and springs.